2015
DOI: 10.1089/omi.2014.0087
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Metabolomics: Metallothioneins Protect Against High-Fat Diet-Induced Consequences in Metallothionein Knockout Mice

Abstract: Obesity continues to rise as an alarming global epidemic. System level mechanisms, diagnostics, and therapeutics are sorely needed so as to identify at risk individuals and design appropriate population scale interventions. The present study evaluated the protective role of metallothioneins (MTs) against obesity and high-fat diet-induced effects such as insulin resistance in both male and female MT-1+2 knockout and MT-3 knockout mice. As the metabolome is closest to the functional phenotype, changes in metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Metabolomics has found recent broad applications in both preclinical and clinical research (Embade et al, 2016;Kim et al, 2011;Lindeque et al, 2015;Lopes et al, 2015). The metabolome, one of the end products of gene-environment interactions immediately upstream to their phenotypic impacts, can help characterize and discriminate pathophysiological signatures of AD (Sapkota et al, 2015), PD (Hatano et al, 2016), and ALS (Blasco et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics has found recent broad applications in both preclinical and clinical research (Embade et al, 2016;Kim et al, 2011;Lindeque et al, 2015;Lopes et al, 2015). The metabolome, one of the end products of gene-environment interactions immediately upstream to their phenotypic impacts, can help characterize and discriminate pathophysiological signatures of AD (Sapkota et al, 2015), PD (Hatano et al, 2016), and ALS (Blasco et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…showed that MT3 KO mice significantly increased their body weight through the intake of a HFD compared with wild type mice. [17] Male hybrid MTKO mice (129/Ola and C57BL/6J background) and MT3 KO (C67/BL6 and 129/Sv background) exhibited obesity. [18,19] Interestingly, these KO mice already had a higher body weight than the wild type (WT) mice at age 3–4 months old, i.e., prior to HFD feeding.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Interestingly, these KO mice already had a higher body weight than the wild type (WT) mice at age 3–4 months old, i.e., prior to HFD feeding. [17] Therefore, MTs may be involved in the regulation of the number of adipocytes and WAT formation at earlier stages, which would contribute to later obesity induced by HFD feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle, diet, and pharmacotherapies account for less than 10% excess weight loss (Khan et al, 2015). However, bariatric surgery is indicated only for patients with morbid obesity (body mass index [BMI] >40 kg/m 2 ) or in cases of moderate obesity associated with comorbidities, particularly the type 2 diabetes (Bruce and Mitchell, 2015;Lindeque et al, 2015).…”
Section: Introductionmentioning
confidence: 99%